2010
DOI: 10.1007/s10800-010-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic inactivation and removal of algae with TiO2-coated materials

Abstract: The capabilities of TiO 2 -coated materials for the inactivation and removal of algae were investigated. As supports for TiO 2 , non-woven fabric and Ni foam were chosen. To evaluate the ability of noble metal cocatalyst additions to facilitate the photocatalytic algal inhibition of TiO 2 -coated materials, Pd nanoparticles were deposited on non-woven fabric-supported TiO 2 by photoelectrochemical deposition. The fabric-supported Pd/TiO 2 showed higher inhibition activity for algal growth compared to the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…On the other hand, the SEM images of the fabric after modification with the host UV-responsive photocatalyst, TiO 2 P 25, are shown in Figure 1b, evidencing that the TiO 2 films are made up of sub-micron particles. These fabrics show a similar morphology with fabrics that we previously prepared and analysed by SEM and X-ray diffraction (XRD) [13]. The SEM images of the fabrics embedded with Fe/TiO 2 and Cu/WO 3 , the visible-light-responsive photocatalysts, are shown in Figure 1c,d, respectively.…”
Section: Introductionsupporting
confidence: 62%
“…On the other hand, the SEM images of the fabric after modification with the host UV-responsive photocatalyst, TiO 2 P 25, are shown in Figure 1b, evidencing that the TiO 2 films are made up of sub-micron particles. These fabrics show a similar morphology with fabrics that we previously prepared and analysed by SEM and X-ray diffraction (XRD) [13]. The SEM images of the fabrics embedded with Fe/TiO 2 and Cu/WO 3 , the visible-light-responsive photocatalysts, are shown in Figure 1c,d, respectively.…”
Section: Introductionsupporting
confidence: 62%
“…It is reported that powder photocatalysts are hard to be gathered and then affect its recycle in the process of governance of water pollution. So, designing active materials in situ grown on macroscopic Ni foam would overcome this problem effectively 25 . Moreover, Nickel foam substrate can be used not only as a reinforcement to enhance conductive performance and promote penetration of electrolytes in the practical application, but also as Ni source during the materials producing process 26 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of photocatalytic technology has completely altered the dilemma of disposing of dye wastewater and has made a difference in the protection of human water resources. [1][2][3][4][5][6][7][8] Since the innovation of photocatalytic technology in 1972, public interest in photocatalysis has continued unabated. 9 With the deepening of research, photocatalysis technology can not only produce hydrogen, but also effectively degrade water pollution.…”
Section: Introductionmentioning
confidence: 99%